The Influence of Profit Management and Corporate Governance on Tax Aggressiveness - Ambarita, Dinar; Febyana, Lidya (Journal of Business Social and Technology, 2025)
This research aims to determine and evaluate the influence of earnings management and corporate governance on tax aggressiveness. This type of research is associative quantitative. The data used is secondary data. The population in this research is food and beverage sub-sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The sample data collection technique in this study used purposive sampling, namely a technique that takes into account criteria, so that the sample obtained using this method was 9 companies. The data analysis technique used is panel data regression analysis using E-views 9 software. The research results show that earnings management and corporate governance influence tax aggressiveness. Then, partially earnings management has no effect on tax aggressiveness. Meanwhile, corporate governance variables influence tax aggressiveness. This result is because the higher the corporate governance, the lower the level of tax aggressiveness taken by the company